The EU’s Anti-SLAPP Directive: A Partial Victory for Rule of Law Advocacy in Europe - Justin Borg-Barthet; Francesca Farrington (German Law Journal)
Strategic Lawsuits Against Public Participation or SLAPPs are abusive lawsuits which have the purpose or effect of suppressing public participation. This Article considers the peculiarities of this form of “strategic litigation” and takes stock of developments in the European Union to combat SLAPPs, noting that while the adoption of an Anti-SLAPP Directive represents an example of effective legal mobilization and a major positive step towards safeguarding the rule of law in the EU, its limitations render it crucial that Member States treat the Directive as a foundation and build national legislation which is more robust in substance and more far-reaching in scope.